The legal Concept of Bank Fusion (Comparative Study) - Tariq Jaafar , Shatha; Omar Mohamed, Prof.Dr.Alaa (Basra studies journal, 2023)
Banking legislation is one of the most important legislation in the modern era because, banks are prevented from An important role in the movement of trade and capital which is beyond the economic basis of any country. Since, the economy is linked to the movement of capital in the global market legislation must be in any country integrated with international legislation taking in to account the higher interests of that country and higher interests of that country and the importance of the study lies comparison between Iraqi banking legislation and banking legislation in relatively developed regional countries in this field there is an opportunity to evaluate this legislation fill the gaps and develop the banking business so it was not it is necessary to shed light on the concept of bank merger in general and the legal concept of it in particular and knowing the characteristics that distinguish it from similar systems in order to establish a legal organization in Iraq is similar to the developed countries in this field to enable it to reach the ranks of the world countries.